Sell in May and go away : adage or self-fulfilling prophecy ? - Santos, António Maria Barahona da Silva Martins dos (2013)
The purpose of this paper is to explore the “Sell in May” effect, which is related to the fact that financial markets seem to provide positively significant returns from November to April and not significant or negatively significant returns from May until October. The Sell in May effect is present in 30 out of 37 indexes, using a sample of 37 country indexes from 1970 to 2011. All sectors of activity are consistently affected by this seasonal pattern, being the effect stronger in production related sectors. The effect is largely felt in high market capitalization companies and less in companies with high dividend yield, being that there is not any clear pattern regarding Price-Earnings ratio. Furthermore, a strategy developed taken into account the “Sell in May” effect outperforms the benchmark, providing higher risk-adjusted returns for an investor.